Kebijakan Pengelolaan Keuangan Terhadap Klaim Bpjs Kesehatan Rawat Jalan Di Rumah Sakit Type C(Studi Komparatif antara Rumah Sakit Swasta X dan Rumah Sakit Umum Daerah Y di Kota Bandung) - Finny Yulianti (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Politeknik Al Islam Bandung, 2025)
The issue of BPJS Kesehatan claim management in type C hospitals present a significant challenge to the healthcare system in Indonesia's. Partner hospitals of BPJS Health often face problem such as delays in claim payments, data mismatches within the INA-CBG’s system, and differences in administrative efficiency between private and public hospitals. These delays negatively affect hospital cash flow and the quality of services provided to BPJS participants. This study aims to analyze financial management policies related to outpatient B -PJS claim disbursement using a qualitative approach and comparative method. Data were collected through interviews, observations, and documentation involving finansial managers, BPJS Health claim officers, deputy directors, and hospital directors as research subjects. The objects of study include private and public type C hospitals in Bandung City. Data analysis was conducted using NVivo software for coding and thematic identification. The results show that private hospitals have more efficient claim administrative systems compared to public hospitals, which often experience delays in claim verification and more complex bureaucratic processes. The main factors contributing to claim disbursements delays include data incosistencies, limited understanding of regulations, and insufficient human resource capacity. The study recommends improving administrative systems, enhancing human resource competencies, and refining regulations as